Technology, Users, and Sustainable Social Housing (European Journal of Formal Sciences and Engineering, 2023)
This paper aims to contribute with results in relation to the challenges that users encounter with regard to technologies in sustainable social housing. The results are significant and show that in modern Danish sustainable social housing consideration is not taken for the users in relation to the technologies implemented in the buildings. The consequences are that the intentions of the technologies supporting economic, environmental, and social sustainability do not work for the users when the buildings are taken into use. The paper argues that developers and architectural practice should in future use simpler technologies that give residents the opportunity to individually regulate their homes’ indoor climate. At the same time, architecture and technology should reflect the consideration towards the climate in the local context and the users’ funda-mental living conditions. The paper argues for the development of a more user-oriented architecture, where the interaction between architecture and technology can work for the users and to a greater extent support the intentions with regard to sustainability.
Keywords: technology, sustainability, architecture, users, interviews, phenomenology